The contributions of health care management to grand health care challenges - Hefner, Jennifer L.; Nembhard, Ingrid M. (Emerald Publishing Limited, 2021)
The 20th volume of Advances in Health Care Management showcases how health care management research helps to further understand grand challenges in health care: what they are, why they exist, the consequences that they have, and what can be done to address them. Grand challenges are large, unresolved problems. "Grand health care challenges" include current events such as the COVID-19 pandemic, and ongoing challenges related to the quadruple aim of health care: improving the health of populations, reducing the cost of healthcare, improving patient care experiences, and improving the experience of working in health care. The book demonstrates that these challenges are amenable to organizational and managerial solutions, and therefore health care management research has many important lessons to contribute. For this volume, The Contributions of Health Care Management to Grand Health Care Challenges, we define health care management as the planning, direction, and coordination of health services and the management of health care professionals. Included chapters consider five grand challenges facing the health care sector: (1) caring for vulnerable populations; (2) maintaining the health care workforce; (3) translating innovation into practice; (4) sustaining organizations; and (5) navigating pandemics. Each challenge is discussed in its own section and addressed by two chapters that offer different perspectives and approaches to the challenge. Across chapters a variety of methodologies are used including ethnographic case studies, survey data analysis, interviews, literature review, and informed commentary. Together, the chapters in this volume synthesize current information in the field, direct future research efforts, and generate actionable insights for managers and policymakers.
Includes index.
Keywords: Health services administration.; Business & Economics -- Industries -- Healthcare.; Medical administration & management.; elektronické knihy; electronic books